User satisfaction with Brazilian public dental services: a systematic review (Research, Society and Development, 2020)
Objective: Developing a review of the scientific literature to measure the satisfaction of users of public dental services in Brazil. Methodology: A systematic review was performed including seven databases (PubMed, Scopus, LILACS, SciELO and Web of Science), including two to capture “gray literature” (OpenGrey and OpenThesis). The risk of bias of included studies was assessed with a specific tool and the data analysis was performed descriptively. Results: 7,689 records were identified and, of these, 11 were included after the selection and application of the eligibility criteria. Most studies had a low risk of bias. The included studies evaluated 4,131 users, of which 85.43% were satisfied. Conclusion: The systematic review pointed to a good level of satisfaction and made it possible to understand the instruments for assessing user satisfaction.